2006
DOI: 10.1007/s11145-006-9014-1
|View full text |Cite
|
Sign up to set email alerts
|

Using the known to chart the unknown: A review of first-language influence on the development of English-as-a-second-language spelling skill

Abstract: Currently, there is a practical demand and necessity for research on how English-as-a-second language (ESL) learners acquire literacy skills, such as spelling. One important issue of this research agenda is how ESL learners apply first-language knowledge to learning to spell in English. Twenty-seven studies were reviewed that investigated the influence of the first language on ESL learners' development of English spelling skill. Evidence was found for both positive and negative transfer of first-language knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 77 publications
6
64
0
1
Order By: Relevance
“…However, common procedural elements may become fewer and transfer less likely as skills become more highly specialised (Henry 1968). Study of skill transfer has many applications in applied psychology and sports science (Taylor et al 2005;Figueredo 2006;Osman 2008). For example, students trained to juggle a football with the feet performed better than controls at juggling with the knees after subsequent training (Weigelt et al 2000).…”
Section: Memory Systems and Skill Transfermentioning
confidence: 99%
“…However, common procedural elements may become fewer and transfer less likely as skills become more highly specialised (Henry 1968). Study of skill transfer has many applications in applied psychology and sports science (Taylor et al 2005;Figueredo 2006;Osman 2008). For example, students trained to juggle a football with the feet performed better than controls at juggling with the knees after subsequent training (Weigelt et al 2000).…”
Section: Memory Systems and Skill Transfermentioning
confidence: 99%
“…The studies available about the connection between first and second language spelling are relatively scarce in comparison to the body of research available about spelling in English as a first language. The findings from the studies conducted on native English speakers cannot be generalized on second language learners of English because the two groups go through different literacy acquisition processes as they learn English (Figueredo, 2006). Nevertheless, the limited available body of research about the relationship between first and second language has repeatedly shown that phonological awareness in first language highly correlates with reading and spelling in a second language, and therefore, it is a good predictor of these skills (e.g., Abu-Rabia & Siegel, 2002;Chen, Kao, & Wei, 2008;Gottardo, Yan, Siegel, & Wade-Woolley, 2001;Sparks, Patton, Ganschow, & Humbach, 2009;Sparks, Patton, Ganschow, Humbach, & Javorsky, 2006, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…If the new language of instant messaging is truly a new or a complementary language (e.g., Crystal, 2006;Lewis & Fabos, 2005), then we might expect both positive and negative transfer between the two ''languages'' (Figueredo, 2006;Sparks, Patton, Ganschow, Humbach, & Javorsky, 2008) based on interdependencies between the two languages (Cummins, 1979). Good spellers in conventional English might make greater use of new language compared with poorer spellers.…”
Section: Introductionmentioning
confidence: 99%